(untitled) (African Journal of Biomedical Research, 2023)
Emergence agitation is a common post-operative complication in children following the use of inhalational anaesthetic agents. The study was designed to evaluate the effects of Ketofol TIVA and isoflurane on the incidence and severity of Emergence Agitation (EA) in children who had cataract surgery. Ninety-four patients between the ages of two and six years with American Society of Anaesthesiologist (ASA) physical status 1 or 11 undergoing elective cataract surgery under general anesthesia were randomised into two groups of 47 patients each. Induction of anaesthesia was with 2-3 mg/kg of propofol in both groups. One group of patients (group A) was maintained with ketofol TIVA in the ratio of 1:10 (1mg/kg/hr of ketamine and 10mg/kg of propofol) while the second group was maintained on 1-1.5 MAC of isoflurane. The incidence and severity of Emergence Agitation (EA) were assessed in the first one hour of the post-operative period using the Paediatric Emergence Delirium (PAED) scale. The emergence, extubation and recovery time were also assessed every 5 minutes and compared using Fisher’s exact test. The complications related to the two techniques of maintenance of anaesthesia in the first hour of the PACU stay were reported. he two groups had similar age and weight characteristics. In group A, 2 patients (4.3%) had EA while 10 patients (21.3%) had same in group B (p<0.005) from baseline time (T0) to 15 minutes postoperatively (T15). The median PAED score was statistically significant at T0 (p = 0.004). There was no statistical difference between the emergence, extubation and recovery times. Retching, vomiting and laryngospasm in both groups were not statistically significant. Ketofol TIVA in the ratio of 1:10 reduced the incidence and severity of EA following cataract extraction in the first one hour of the post-operative period when compared with isoflurane as maintenance anaesthetics.